Current Treatment of Ascending Colon Volvulus in Horses: A Survey of ACVS Diplomates. Issue 3 (14th April 2014) - Fiege, Jamie K.; Hackett, Eileen S.; Rao, Sangeeta; Gillette, Shana C.; Southwood, Louise L.
<x xml:space="preserve">Abstract</x> Objective To report the results of a survey of opinions on current treatments and estimated outcomes of ascending colon volvulus in horses. Study Design Web‐based survey. Sample Population American College of Veterinary Surgeons (ACVS) Diplomates (n = 151) who perform gastrointestinal surgery in horses. Methods ACVS Diplomates with credentials in the large animal specialty obtained by examination in 2010 or earlier (n = 410) were solicited by e‐mail to complete a web‐based survey designed to determine ascending colon volvulus treatment preferences and outcomes. Results Responses were obtained from 162 ACVS Diplomates, of which 151 currently performed gastrointestinal surgery in horses. Horses surgically treated with ascending colon volvulus accounted for ≤20 cases/year and primary treatment was most often anatomic reduction with or without pelvic flexure enterotomy. Median estimated survival rate was 70% and surgical treatments were not associated with estimated survival (P = .27). Diplomates identified early surgical correction as the single most important factor impacting survival of horses surgically treated for ascending colon volvulus. Conclusions Reported survival rates for horses with ascending colon volvulus were good. Respondents indicated this might be due in part to early surgical treatment. Survey investigations can provide preliminary data for future prospective studies and facilitate a consensus among Diplomates in treatment of surgical disease.